THE REBIRTH OF AN OLD LANGUAGE: ISSUES OF GENDER EQUALITY IN KAZAKHSTAN - Guimarães, Maria Helena (POLISSEMA – Revista de Letras do ISCAP, 2019)
The existing language situation in Kazakhstan, while peaceful, is not without some tension. We propose to analyze here some questions we consider relevant in the frame of cultural globalization and gender equality, such as: free from Russian imperialism, could Kazakhstan become an easy prey of Turkey’s “imperialist dream”? Could these traditionally Muslim people be soon facing the end of religious tolerance and gender equality, becoming this new old language an easy instrument for the infiltration in the country of fundamentalism (it has already crossed the boarders of Uzbekistan), leading to a gradual deterioration of its rich multicultural relations? The present structure of the language is still very fragile: there are three main dialects and many academics defend the re-introduction of the Latin alphabet, thus enlarging the possibility of cultural “contamination” by making the transmission of fundamentalist ideas still easier through neighbour countries like Azerbaijan, Uzbekistan and Turkmenistan (their languages belong to the same sub-group of Common Turkic), where the Latin alphabet is already in use, and where the ground for such ideas shown itself very fruitful.